Comparison of mechanical and wearing properties between LM13 matrix and Stir cast LM13/B4C/Gr hybrid composites of various composition - Faisal, M.H.; Prabagaran, S.; Vishnu, T.S. (International Journal of Engineering and Technology, 2017)
Aluminium/graphite composites are the need of modern times for addressing the fuel saving issues. The graphite in such composites act as solid lubricant and it reduce external fuel requirements. But such composites are having degraded mechanical properties due to the graphite content in composite. In order to solve the negative effect of graphite on mechanical properties of LM13/Gr self-lubricating composite this study was conducted to find out the mechanical properties of LM13/B4C/Gr Metal Matrix Composites. Boron carbide was selected as reinforcement because of its better reinforcement properties compared to alumina and silicon carbide. The properties of the hybrid composites were compared with the LM13/Gr self-lubricating composite to study the enhancement in mechanical properties that has been caused by the boron carbide particles. Using computerized universal testing machine and rock-well hardness tester mechanical properties such as hardness and tensile strength were tested. Pin on disk testing machine was used to analyse the wear behavior. The test results indicates that by raising weight % of boron carbide particles in the LM13, tensile strength and hardness of the hybrid composites was increased compared to self-lubricating composite accompanied by better tribological properties.